2016
DOI: 10.1111/jocn.13283
|View full text |Cite
|
Sign up to set email alerts
|

Motives that head and neck cancer patients have for contacting a specialist nurse – an empirical study

Abstract: When implementing a specialist nurse function, it is important to decide whether the function should be inspired by a broader relational perspective. In addition to the indispensible competence and experience in the clinical field of head and neck cancer, training in counselling and acquaintance with object-relational psychology will then be desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Written informed consent was obtained from all of the patients, and the study was reviewed and approved by the Regional Ethical Review Board in Umeå (Dnr 2010-24-31). Four articles have previously been published from the material obtained from the clinical development programme (Isaksson, Salander, Granström, & Laurell, 2014;Isaksson, Wilms, Laurell, Fransson, & Ehrsson, 2016;Salander, Isaksson, Granström, & Laurell, 2016;Stenhammar, Isaksson, Granström, Laurell, & Ehrsson, 2017).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Written informed consent was obtained from all of the patients, and the study was reviewed and approved by the Regional Ethical Review Board in Umeå (Dnr 2010-24-31). Four articles have previously been published from the material obtained from the clinical development programme (Isaksson, Salander, Granström, & Laurell, 2014;Isaksson, Wilms, Laurell, Fransson, & Ehrsson, 2016;Salander, Isaksson, Granström, & Laurell, 2016;Stenhammar, Isaksson, Granström, Laurell, & Ehrsson, 2017).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Such a predictive ability would also encourage survivors and caregivers to report their unmet needs and allow us to improve the efficiency of the care provided and make decisions based on survivors'/caregivers' individual preferences. A few studies suggested a relationship between cancer type and specific unmet needs [16,[18][19][20], while the present study focused on the relationship. In clinical practice, cancers are conventionally dealt with by each category for the affected organ.…”
Section: Introductionmentioning
confidence: 83%
“…This result is not consistent with those of previous studies, which suggested strong relationships between specific cancer types and specific unmet needs. For example, several studies have reported that breast-cancer survivors tend to have psychosocial needs [12,[18][19][20].…”
Section: Small Effects Of Specific Cancer Typesmentioning
confidence: 99%
“…There is a need for expertise in HNC care and training in counselling and relational psychology (Salander et al, 2016), particularly as there is a lack of knowledge about HNC and the psychological consequences, and psychological interventions have every chance of improving people's ability to feel happiness. The microflow component oral when snacking or chewing was seldom used on account of pain, trismus or an inability to chew.…”
Section: Discussionmentioning
confidence: 99%